A SPICE model for design of threshold current controlled memristive devices based applications - Dias, Cesar de Souza (2021)
This paper presents a generic SPICE model for threshold current controlled memristive devices. This work relates to mathematical development to allow this kind of behavior and it exhibits its relationship with the equivalent circuit adopted to achieve this goal. The operating logic is described and the code for its computational implementation is presented and explained. The functionality of the model implemented is demonstrated through several simulation experiments, whose results clearly show the switching resistance dependency on the electrical current through the device and highlight some important fingerprints of memristive devices. The acquisition and the data analysis from tests also help to prove the excellent convergence performance of the model presented and to elucidate the parameter settings. Finally, the paper reinforces the relevance of this new proposition by addressing one of its potential applications, demonstrating its use in the implementation of memristive stateful logic based on material implication.